Cobertura florestal e disponibilidade hídrica na bacia do ribeirão do Espírito Santo em Juiz de Fora-MG - Oliveira, Paulo Henrique dos Santos (2009)
The present dissertation has as the main objective to evaluate the relation between the vegetable covering and the water availability in the basin of the Espírito Santo Creek, second greatest source of water supply of the city of Juiz de Fora, located in Minas Gerais. The work in question was accomplished from the application of the Model of Cells of Drainage, developed by the Hydrology Laboratory that belongs to the Coordination of UFRJ Engineering Post Graduation Programmes, loaded with information from the Geographical Information System. In the end we could conclude that the forest recovery of the basin would produce an increase of 8 % in the outflow of the refered creek without, however, reaching the outflow needed to achieve the goals from the Managing Plan of Water Supply of Juiz de Fora for the year of 2011.We could also conclude that the forest resetting would be essential for the maintenance of minimum standards of quality of the water distributed in Juiz de Fora.